Evaluation of Crack Initiation Points of Load-Carrying Cruciform Welded Joints Based on Effective Notch Stress Approach - Kinoshita, K.; Arakawa, S. (Institute of Research and Community Outreach - Petra Christian University, 2014)
For fatigue assessment, recently effective notch stress (ENS) approach is accepted as a valid alternative to fracture mechanics approaches in Japan. However, at least one study showed that the fatigue assessment at weld root of load-carrying cruciform welded joints based on ENS approach does not capture the influence of plate thickness, weld size and weld penetration. Consequently, there are still uncertainties about the fatigue assessment. This paper discusses the evaluation method of the joints based on ENS approach. Effects of weld size, weld penetration, and plate thickness on ENS are determined by using fine-meshed FEM analyses. Validity of this method is determined by comparing the evaluation results with fracture mechanics approach. It is shown that results from this method are comparable to those of the previous study and the results seem to be conservative when ratio of weld penetration to plate thickness becomes smaller and plate thickness becomes larger.